Analysis of workload, work environment, and work stress on nurse performance - Arif Widiyantoro; Jenny Marlindawani Purba; Mido Ester Sitorus (Nursing and Health Sciences Journal (NHSJ), 2025)
The decline in nurse performance significantly affects the service image of a hospital in the community. Poor nursing services lead to a lack of public confidence in the hospital's capabilities. The low quality of nursing services can be caused by many factors, such as the quality of nurses' working lives and burnout syndrome. High work handled by a few human resources will only result in a high workload and increased work stress. A conducive work environment not only helps nurses control stress but also allows them to improve their performance. Researchers aim to analyze the workload, work environment, and work stress on the performance of nurses. The number of samples used was 141 nurses who were willing to be respondents and not in a state that could affect data collection. The dependent variable is nurse performance, and the independent variables are workload, work environment, and work stress. Data was analyzed using the Chi-Square Analysis method with the SPSS 19.0 for Windows program. The results showed that the workload variable did not affect nurse performance, with a p-value of 0.513; the work environment variable affected nurse performance, with a p-value of 0.013; the work stress variable did not affect nurse performance, with a p-value of 0.484. The results indicate that the work environment is the only factor significantly associated with nurse performance among the variables examined. These findings suggest that interventions to improve nurse performance should prioritize optimizing the work environment. Work workload and work stress, as measured in this study, may not require targeted adjustments for performance enhancement.